Šeimos Lietuvos partizaniniame kare: Dešinio tėvūnijos (1949–1953 m.) atvejis - Karaliūtė, Emilija (Genocidas ir rezistencija, 2024)
The purpose of this study is to analyse the relationship of the participants of the armed underground resistance with their families after they decided to become partisans and after they actually became partisans, to include discussion of how such a decision changed the fate of their loved ones.The existing sources hint at three possible reactions of any family to the decision of one of its members to join the armed anti-Soviet resistance: such a person might be blessed with a prayer (and a cross) with kneeling; but there were also chaotic reactions. But, in any case, having to saying goodbye to loved ones did not change the decision of those who went ahead with it. Family members, regardless of whether they expressed approval of or opposition to such a decision, often naturally became involved in underground activities.The case of Dešinys Group (tėvūnija) reveals the importance of families in the Lithuanian fight for freedom and the extent to which relatives were involved – with a unit as small as the Dešinys Group, according to this investigation, 66.7% of the individuals of these five families became fighters or their informants. In the Lithuanian fights for freedom, these five families in it lost 16 children, and not a single relative was left untouched by the Soviets – all of them were exiled or forced to hide.
Keywords: Lithuanian fights for freedom; partisans; deportation; Dešinys Group